Improvement of the thermoelectric performance of InSe-based alloys doped with Sn. Issue 124 (30th November 2015) - Hou, Xiaojing; Chen, Shaoping; Du, Zhengliang; Liu, Xianglian; Cui, Jiaolin
Abstract : Sn preferentially occupies In sites, which creates a defect SnIn + and intermediate band, thus tailoring the thermoelectric performance of InSe. Abstract : Here we present InSe-based alloys InSeSn x ( x = 0–0.02) with improved thermoelectric performance upon Sn's preferential occupation on In lattice sites. This improvement is attributed to the enhancement in carrier concentration ( n ) and reduction in lattice thermal conductivity ( κ L ). However, the enhancement in n is limited due to the presence of the intermediate band in the middle of the bandgap, which acts as an annihilation center for electrons and holes. The reduction in κ L is caused by increased phonon scattering on the newly-created defect SnIn + . As a result, we attain the highest ZT value of 0.23 at x = 0.01@830 K, which is about 2.9 times that of virgin InSe.